Adopting Work-style Reforms, Promoting the Inclusive Workplace: Japan’s Strategies on the Diversifying Labor Market - Firman Budianto (KIRYOKU, 2021)
As a response to the diversifying labor market, the government of Japan has released a set of policies to foster productivity and increase participation of not only women but also seniors, people with disabilities, and foreigners in the country’s job market. However, the literature on the diversification of Japan’s labor force has paid little attention to the Japanese government’s perspectives on this issue. This qualitative study, therefore, examines the current Japanese government’s strategies in regards with the changing domestic labor market and workplace through critical analyses of the government’s policies and publications. This study observed that the government of Japan has set out to adopt work-style reforms and promote an inclusive workplace for everyone. These two key policies should address the inequality and the work-life balance issues as the core obstacle in Japan’s business practices. This present study suggests that fundamental reforms in the way Japanese people work might pave the way to solving the country’s economic and sociocultural challenges that, to some extent, are rooted in the structural problems in the workplace.